Leaf Area Influences Photosynthetic Activities, Raisin Yield and Quality in Manjari Kishmish Grape Variety - R. G. Somkuwar; P. B. Kakade; J. K. Dhemre; P. S. Gharate; N. A. Deshmukh; P. H. Nikumbhe (Archives of Current Research International, 2024)
The ideal leaf area is essential for optimizing photosynthesis and resource distribution, which improves both yield and quality. Leaf retention is a cultural practice that involves maintaining definite number of leaves above the bunch to optimize photosynthetic efficiency and fruit quality. The experiment was conducted at the ICAR-National Research Centre for Grapes with different treatments of number of leaves above the bunch (10, 12, 14, 16 and >16 leaves). The parameters measured included leaf area, photosynthetic rate, stomatal conductance, transpiration rate, bunch weight, berry quality and raisin recovery. The results revealed that retaining 14 leaves above bunch with leaf area of 1066.33 cm2 resulted in maximum bunch weight (365.00 g), 50-berry weight (123.31 g), yield/vine (23.72 kg) and raisin recovery (26.54 %) while, minimum bunch weight (300.00 g), 50-berry weight (103.48 g), yield/vine (19.20 kg) and raisin recovery (24.35 %) were observed in more than16 leaves above the bunch. However, the leaf area/shoot (2888.00 cm2), leaf area/vine (69312.00 cm2), leaf area/bunch (1066.33 cm2) and leaf area/g berry weight (2.92 cm2/g) were found sufficient for high quality grape and raisin production in a vine spaced at 9 X 5 feet distance which was achieved through 14 leaves above the bunch in Manjari Kishmish grape. It is therefore recommended to maintain approximately 14 leaves above the bunch in Manjari Kishmish that will help to maximize photosynthetic efficiency, enhance leaf area distribution and support higher yield, raisin and better berry quality.